2021
DOI: 10.1080/15476286.2021.1950980
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional insights into human tRNA guanine transglycosylase

Abstract: S 1 Q-incorporation into stem loop RNA Q-incorporation by human TGT into tRNA Asp , a tRNA Asp anticodon stem loop or the Y32U33G34U35 stem loop construct used for crystallization. The incorporation reactions contained either 4 µM tRNA or 5 µM stem loop RNA, 1 mM queuine and 0.5 to 10 µM TGT and were incubated for 1 h (tRNA Asp ) to 2.5 h (stem loops) at 37 °C. Reaction samples were separated on a boronate affinity electrophoresis gel, which causes retardation of queuine-containing RNA through interaction via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…The crystal structure of h QTRTD1 (also called QTRT2) revealed that h QTRTD1 forms a homodimer with striking similarity to that of bacterial TGT ( Behrens et al, 2018 ). Recently, the crystal structure of hTGT in its heterodimeric form and in complex with a 25-mer stem loop RNA has been established ( Sievers et al, 2021 ). The detailed analysis of its dimer interface and interaction with a minimal substrate RNA indicates that one base only, guanine 34 or queuine, can simultaneously reside at the active site in support to a “ping-pong” mechanism that has already been proposed for E.coli TGT ( Goodenough-Lashua and Garcia, 2003 ).…”
Section: Current Knowledge Of the Epigenetic Mechanisms Characterized...mentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structure of h QTRTD1 (also called QTRT2) revealed that h QTRTD1 forms a homodimer with striking similarity to that of bacterial TGT ( Behrens et al, 2018 ). Recently, the crystal structure of hTGT in its heterodimeric form and in complex with a 25-mer stem loop RNA has been established ( Sievers et al, 2021 ). The detailed analysis of its dimer interface and interaction with a minimal substrate RNA indicates that one base only, guanine 34 or queuine, can simultaneously reside at the active site in support to a “ping-pong” mechanism that has already been proposed for E.coli TGT ( Goodenough-Lashua and Garcia, 2003 ).…”
Section: Current Knowledge Of the Epigenetic Mechanisms Characterized...mentioning
confidence: 99%
“…The detailed analysis of its dimer interface and interaction with a minimal substrate RNA indicates that one base only, guanine 34 or queuine, can simultaneously reside at the active site in support to a “ping-pong” mechanism that has already been proposed for E.coli TGT ( Goodenough-Lashua and Garcia, 2003 ). Regarding hQTRTD1, the authors proposed that it could serve to anchor the TGT enzyme in the compartmentalized eukaryotic cell ( Sievers et al, 2021 ). Based on the annotation of the E. histolytica genome, a homolog of h QTRT1 and h QTRTD1 exists in E. histolytica , namely Eh QTRT1 (XP_656142.1) and Eh QTRTD1 (XP_652881.1).…”
Section: Current Knowledge Of the Epigenetic Mechanisms Characterized...mentioning
confidence: 99%
“…The cyclopentendiol moiety is synthesized at the level of tRNA from unknown precursors and enzymes in both eubacterial and eukaryotic species. The crystal structure of hTGT in its heterodimeric form and in complex with a 25-mer stem-loop RNA has been recently established [ 10 ]. The detailed analysis of its dimer interface and interaction with a minimal substrate RNA indicates that one base only, guanine 34 or queuine, can simultaneously reside at the active site in support of a “ping-pong” mechanism that has already been proposed for E. coli TGT [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cyclopentendiol moiety is synthesized at the level of tRNA from unknown precursors and enzymes in both eubacterial and eukaryotic species. The crystal structure of hTGT in its heterodimeric form and in complex with a 25-mer stem loop RNA has been recently established [8]. The detailed analysis of its dimer interface and interaction with a minimal substrate RNA indicates that one base only, guanine 34 or queuine, can simultaneously reside at the active site in support to a “ping-pong” mechanism that has already been proposed for E. coli TGT [9].…”
Section: Introductionmentioning
confidence: 99%
“…The detailed analysis of its dimer interface and interaction with a minimal substrate RNA indicates that one base only, guanine 34 or queuine, can simultaneously reside at the active site in support to a “ping-pong” mechanism that has already been proposed for E. coli TGT [9]. Regarding hQTRTD1, the authors proposed that it could serve to anchor the TGT enzyme in the compartmentalized eukaryotic cell [8]. Based on the annotation of the E. histolytica genome, a homolog of h QTRT1 and h QTRTD1 exists in E. histolytica , namely Eh QTRT1 (XP_656142.1) and Eh QTRTD1 (XP_652881.1).…”
Section: Introductionmentioning
confidence: 99%